Blood Macro and Micro Mineral Status of Calves During Treatment for Industrial Fluorosis with Tamarind (Tamarindus indica) Fruit Pulp - Pati, M.; Parida, G. S.; Mandal, K. D.; Gupta, A. R.; Swain, R. K.; Senapati, S. K.; Patra, R. C. (Indian Journal of Animal Nutrition, 2018)
The present investigation was carried out to examine the mineral status in fluorotic calves reared around the vicinity of aluminium smelter plant during treatment with Tamarindus indica fruit pulp. Eighteen calves of 6-12 months age having average body wt of 81.2 kg were selected. Group T1 calves (n=6) from fluoride free area served as healthy controls. Twelve calves with typical dental lesion of fluorosis and high plasma F level were selected from the industrial fluorosis affected area (having toxic level of F in soil, water and fodder samples) and were divided in two equal groups consisting of 6 animals each. Group T2 animals received no treatment and served as disease control and group T3 animals were given tamarind pulp powder (79.3% DM) @ 30 g/calf/day for a period of 60 days. Blood samples were collected from the animals of all the groups on day 0, 30 and 60 of the experiment for estimation of macro (Ca, P and Mg) and micro (Fe, Zn, Mn and Co) minerals. Significantly (P<0.05) higher level of P and Co and lower level of Ca, Mg, Fe, Zn and Mn were observed in calves with higher plasma fluoride level in T2 and T3 with respect to T1 at the beginning of experiment. Reduction of 66% in plasma fluoride level in calves of group T3 receiving tamarind for a period of 60 days was associated with significant (P<0.05) reduction in levels of P and Co and rise in Ca, Mg, Fe and Zn in comparison to group T2 while Mn levels remained unaltered. However, at d 60, the concentration of F, macro and micro minerals was comparable with T1. It was concluded that dried pulp powder of tamarind ameliorated the blood mineral profile altered by chronic exposure to fluoride.